2020
DOI: 10.1002/jcla.23415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical features and outcomes of 161 patients with severe and critical COVID‐19: A multicenter descriptive study

Abstract: Background This study aimed to investigate clinical characteristics, laboratory indexes, treatment regimens, and short‐term outcomes of severe and critical coronavirus disease 2019 (COVID‐19) patients. Methods One hundred and sixty one consecutive severe and critical COVID‐19 patients admitted in intensive care unit (ICU) were retrospectively reviewed in this multicenter study. Demographic features, medical histories, clinical symptoms, lung computerized tomography (CT) findings, and laboratory indexes on admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 16 publications
4
34
0
2
Order By: Relevance
“…The highest country-specific mortality from COVID-19 associated ARDS was found in China, which may be due to a lack of understanding of the origin and pathophysiology of the infection by SARS-CoV-2, as well as its management during the early outbreak of COVID-19. Of the 19 original Chinese studies included, all but two are originated in Hubei province (Wuhan is the capital city of Hubei province) [31][32][33][34][35][36][39][40][41][44][45][46][48][49][50]52,53], the epicenter of the COVID-19 outbreak. In fact, the study of Chen N et al [32] included a cluster of patients (49% of total patients included) who had a history of exposure to the Huanan seafood market, which is referred to as the 'ground zero' of the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The highest country-specific mortality from COVID-19 associated ARDS was found in China, which may be due to a lack of understanding of the origin and pathophysiology of the infection by SARS-CoV-2, as well as its management during the early outbreak of COVID-19. Of the 19 original Chinese studies included, all but two are originated in Hubei province (Wuhan is the capital city of Hubei province) [31][32][33][34][35][36][39][40][41][44][45][46][48][49][50]52,53], the epicenter of the COVID-19 outbreak. In fact, the study of Chen N et al [32] included a cluster of patients (49% of total patients included) who had a history of exposure to the Huanan seafood market, which is referred to as the 'ground zero' of the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited data was available, we managed to retrieve mortality data in COVID-19 patients with ARDS from six countries in addition to China and improved the reliability of the analysis presented in this article. Nevertheless, original studies that reported mortality in COVID-19 patients with ARDS with inadequate duration of follow-up [32,36,39,43,48,54,59,61,62] may have underestimated the mortality rate than if followed up until defintite outcome (death/discharged).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbidities may exacerbate the patient's condition. Shi et al 7 reported that hypertension and diabetes were most common in severe and critical COVID‐19 patients. Chen et al 5 reported 50% of patients had underlying diseases including cardiovascular disease, diabetes, and gastrointestinal disease, and such patients were more likely to deteriorate or have poor prognoses.…”
Section: Discussionmentioning
confidence: 99%